Adapting psychophysiological data collection for COVID‐19: The "Virtual Assessment" model. Issue 1 (21st December 2021) - Tabachnick, Alexandra R.; Sellers, Tabitha; Margolis, Emma; Labella, Madelyn; Neff, Dylan; Crowell, Sheila; Raby, K. Lee; Saenz, Celine; Conradt, Elisabeth; Dozier, Mary
Abstract: The COVID‐19 pandemic has significantly disrupted research activities globally. Researchers need safe and creative procedures to resume data collection, particularly for projects evaluating infant mental health interventions. Remote research is uniquely challenging for psychophysiological data collection, which typically requires close contact between researchers and participants as well as technical equipment frequently located in laboratory settings. In accordance with public health guidance, we adapted procedures and developed novel protocols for a "virtual assessment" in which women and infants provided behavioral and psychophysiological data from their own homes while researchers coordinated remotely. Data collected at virtual visits included video‐recorded parent–child interactions and autonomic nervous system data. Adaptations were designed to optimize safety and data quality while minimizing participant burden. In the current paper, we describe these adaptations and present data evaluating their success across two sites in the United States (University of Delaware and University of Utah), focusing specifically on autonomic nervous system data collected during the well‐validated Still‐Face Paradigm (SFP). We also discuss advantages and challenges of translating traditional lab procedures into the virtual assessment model. Ultimately, we hope that disseminating these procedures will help other researchers resume safe data collection related to infant mental health during the COVID‐19 pandemic and beyond. Resumen: La pandemia del COVID‐19 ha interrumpido significativamente las actividades de investigación globalmente. Los investigadores necesitan procedimientos seguros y creativos para reasumir la recolección de información, particularmente para proyectos con los que se evalúan intervenciones de salud mental infantil. La investigación remota es particularmente desafiante para recoger información psicofisiológica, lo cual típicamente requiere contacto cercano entre investigadores y participantes, así como también equipo técnico frecuentemente localizado en centros de laboratorio. De acuerdo con las directrices de salud pública, adaptamos procedimientos y desarrollamos protocolos novedosos para una "evaluación virtual, " en la cual mujeres e infantes aportaron datos de conducta y psicofisiológicos desde sus propias casas mientras que los investigadores coordinaban remotamente. La información recogida en las visitas virtuales incluyó interacciones progenitor‐niño grabadas en video e información del sistema nervioso autónomo. Se diseñaron las adaptaciones para optimizar la seguridad y la calidad de la información mientras que se reducía al mínimo la carga que conlleva la participación. En el presente estudio, describimos estas adaptaciones y presentamos información evaluativa del éxito en dos lugares de Estados Unidos (la Universidad de Delaware y la Universidad de Utah), con enfoque específico en la información obtenida acerca del sistema nervioso autónomo durante el ya bien validado Paradigma del Rostro Inmóvil. Discutimos también las ventajas y retos para transferir los procedimientos tradicionales de laboratorio al modelo de evaluación virtual. En última instancia, esperamos que al diseminar estos procedimientos ayudaremos a otros investigadores a reasumir la segura recolección de información relacionada con la salud mental infantil durante la pandemia del COVID‐19 y posteriormente. Résumé: La pandémie du COVID‐19 a perturbé de manière importante les activités de recherche au niveau global. Les chercheurs ont besoin de procédures sûres et créatives pour reprendre la collecte de données, particulièrement pour des projets évaluant des interventions en santé mentale du nourrisson. Les recherches à distance présentent un défi unique pour la collecte de données psychophysiologiques, qui typiquement exige un contact proche entre les chercheurs et les participants ainsi qu'un équipement technique fréquemment situé en contextes de laboratoire. En accord avec les directives de santé publique nous avons adapté les procédures et développés de nouveaux protocoles pour une « évaluation virtuelle » durant laquelle les femmes et les bébés ont présenté des données comportementales et psychophysiologiques depuis leurs propres domiciles alors que les chercheurs coordonnaient le tout à distance. Les données recueillies durant les visites virtuelles ont inclus des interactions parent‐enfant enregistrées à la vidéo et des données liées au système nerveux autonome. Les adaptations ont été conçues afin d'optimiser la sécurité et la qualité des données tout en minimisant le fardeau pour les participants. Dans cet article nous décrivons ces adaptations et présentons les données évaluant leur succès au travers de deux sites aux Etats‐Unis (University of Delaware et University of Utah), en s'attachant plus spécifiquement aux données sur le système nerveux autonome obtenues durant le Paradigme de Visage Inexpressif, qui est bien validé. Nous discutons également les avantages et des défis qu'il y a à traduire des procédures traditionnelles de laboratoire en un modèle d'évaluation virtuel. Finalement nous espérons que le fait de disséminer ces procédures aidera d'autres chercheurs à reprendre de manière sûre la collecte de données liées à la santé mentale du nourrisson durant la pandémie du COVID‐19 et plus loin. Zusammenfassung: Die Anpassung psychophysiologischer Datenerhebung an COVID‐19: Die „virtuelle Untersuchung" Die COVID‐19‐Pandemie hat Forschungsaktivitäten weltweit erheblich beeinträchtigt. Forschende brauchen sichere und kreative Verfahren, um die Datenerhebung wieder aufzunehmen, insbesondere für Projekte zur Beurteilung von Interventionen zur psychischen Gesundheit von Kindern. Bei der psychophysiologischen Datenerhebung, die in der Regel einen engen Kontakt zwischen Forschenden und Teilnehmenden sowie eine häufig in Laboren befindliche technische Ausrüstung erfordert, stellt die Fernforschung eine besondere Herausforderung dar. In Übereinstimmung mit den Richtlinien des öffentlichen Gesundheitswesens haben wir die Verfahren angepasst und neue Protokolle für eine "virtuelle Untersuchung" entwickelt. Frauen und Säuglinge lieferten von zu Hause aus Verhaltens‐ und psychophysiologische Daten, während die Forschenden diesen Prozess aus der Ferne koordinierten. Die bei den virtuellen Visiten gesammelten Daten umfassten Videoaufzeichnungen von Eltern‐Kind‐Interaktionen und Daten des autonomen Nervensystems. Es wurden Anpassungen vorgenommen, um die Sicherheit und Datenqualität zu optimieren und gleichzeitig die Belastung der Teilnehmenden zu minimieren. Im vorliegenden Beitrag beschreiben wir diese Anpassungen und stellen Daten vor, die ihren Erfolg an zwei Standorten in den Vereinigten Staaten (University of Delaware und University of Utah) untersuchen, wobei wir uns speziell auf Daten des autonomen Nervensystems konzentrieren, die während des gut validierten Still‐Face‐Paradigmas erhoben wurden. Wir erörtern außerdem die Vorteile und Herausforderungen bei der Übertragung traditioneller Laborverfahren in das virtuelle Untersuchungsmodell. Letztendlich hoffen wir, dass die Verbreitung dieser Verfahren anderen Forschenden helfen wird, sichere Datenerhebung im Zusammenhang mit der psychischen Gesundheit von Kindern während der COVID‐19‐Pandemie und darüber hinaus wieder zu ermöglichen. 抄録: COVID‐19に対する精神生理学的データ収集の適応　:「仮想評価」モデル COVID‐19パンデミックは世界的に研究活動の大きな妨げとなった。研究者は、データ収集を再開するための安全で創造的な手順を必要としており、特に乳幼児のメンタルヘルスへの介入を評価するプロジェクトにおいてはその必要性が高まっている。遠隔研究は、研究者と被験者が綿密な連絡を取り合い、実験室に設置されていることの多い技術的な装置を必要とする精神生理学的データ収集には独特の難しさがある。そこで私たちは、公衆衛生上の指針に基づき、女性と乳児が行動や精神生理学的なデータを自宅から提供し、研究者が遠隔で対応するという「仮想評価」の手順を応用し、新しいプロトコルを開発した。仮想訪問で収集されたデータには、ビデオ録画された親‐子の相互作用と自律神経系データが含まれていた。本研究では、参加者の負担を最小限に抑えながら、安全性とデータ品質を最適化するように工夫された。今回の論文では、これらの適応について説明するとともに、米国の2つのサイト (デラウェア大学とユタ大学) における適応の成功を評価するデータを提示し、特に十分に検証された「Still‐FaceParadigm」で収集された自律神経系データに焦点を当てる。我々は、従来の研究室での手順から仮想評価モデルに変換することの利点と課題も検討している。最終的には、これらの手順を広めることで、他の研究者がCOVID‐19パンデミック中やそれ以降の乳児のメンタルヘルスに関連する安全なデータ収集を再開するのに役立つことを願っている。 摘要: COVID‐19大流行严重扰乱了全球的研究活动。研究人员需要安全和创造性的程序来恢复数据收集, 特别是在评估婴儿心理健康干预措施的项目中。远程研究对于心理生理学数据收集来说具有独特的挑战性, 这通常需要研究人员和参与者之间的密切联系以及经常位于实验室环境中的技术设备。根据公共卫生指南, 我们调整了程序并制定了新的"虚拟评估"协议, 其中妇女和婴儿从自己家中提供行为和心理生理数据, 而研究人员则进行远程协调。在虚拟访问中收集的数据包括视频记录的亲子互动和自主神经系统数据。调整旨在优化安全性和数据质量, 同时最大限度地减少参与者的负担。在本文中, 我们描述了这些调整, 并提供了评估其在美国两个地点 (特拉华大学和犹他大学) 成功的数据, 特别关注了在经过充分验证的"静止面孔试验范式"期间收集的自主神经系统数据。我们还讨论了将传统实验室程序转换为虚拟评估模型的优势和挑战。最终, 我们希望, 推广这些程序以帮助其他研究人员在COVID‐19大流行期间及疫后恢复与婴儿心理健康相关的安全数据收集。 ملخص: تكييف نموذج جمع البيانات النفسية والفسيولوجية لكوفيد ‐19: نموذج "التقييم الافتراضي" تسببت جائحة كوفيد‐19 في تعطيل أنشطة البحث بشكل كبير على مستوى العالم. يحتاج الباحثون إلى إجراءات آمنة ومبتكرة لاستئناف جمع البيانات ، لا سيما فيما يتعلق بمشاريع تقييم تدخلات الصحة النفسية للرضع. يمثل البحث عن بُعد تحديًا فريدًا لجمع البيانات النفسية والفسيولوجية ، والذي يتطلب عادةً اتصالًا عن قرب بين الباحثين والمشاركين بالإضافة إلى المعدات التقنية الموجودة في كثير من الأحيان في المعامل. وفقًا لإرشادات الصحة العامة ، قمنا بتكييف الإجراءات وطورنا بروتوكولات جديدة لـ "التقييم الافتراضي" حيث ساهمت النساء والرضع بتقديم بيانات سلوكية ونفسية فسيولوجية من المنزل بينما كان الباحثون ينسقون عن بُعد. تضمنت البيانات التي تم جمعها في الزيارات الافتراضية التفاعلات المسجلة بالفيديو بين الوالدين والطفل وبيانات الجهاز العصبي اللاإرادي. تم تصميم عمليات التكييف لتحسين السلامة وجودة البيانات مع تقليل عبء المشاركين. في هذا البحث ، نصف هذه التعديلات ونقدم البيانات التي تم تقييم نجاحها عبر موقعين في الولايات المتحدة (جامعة ديلاوير وجامعة يوتا) ، مع التركيز بشكل خاص على بيانات الجهاز العصبي اللاإرادي التي تم جمعها خلال نموذج الوجه الثابت الذي تم التحقق من صحته جيدًا. نناقش أيضًا مزايا وتحديات ترجمة إجراءات المعمل التقليدية إلى نموذج التقييم الافتراضي. في النهاية ، نأمل أن يساعد نشر هذه الإجراءات الباحثين الآخرين على استئناف جمع البيانات المتعلقة بالصحة النفسية للرضع بشكل آمن أثناء جائحة كوفيد‐19 وما بعدها.